The knowledge of and attitudes towards HIV/AIDS among post-secondary students in a southern Ethiopian city - Paul, Marianne M. (My University, 2011)
Introduction: The HIV/AIDS epidemic continues to claim millions of lives worldwide. Africa alone represents the majority of HIV/AIDS cases, where the young aged 16-30, are at greatest risk. In Ethiopia, the research suggests that knowledge of HIV transmission and positive attitudes among post-secondary students are decreasing. The purpose of this research is to explore the knowledge and attitudes of HIV/AIDS among post-secondary students in a southern Ethiopian city.
Methods: A cross-sectional study was conducted among 227 college and university students. The AIDS Attitude Scale and the HIV Knowledge Questionnaire were used to measure participants’ knowledge and attitudes on HIV/AIDS. Descriptive statistics, t-test, correlation and regression analysis were used for analysis.
Results: The results from the HIV Knowledge Questionnaire revealed lower knowledge on the various sexual modes of HIV transmission. The t-test demonstrated no difference between male and female HIV knowledge scores (t=0.6, df =225, p=0.4). The correlation analysis indicated a significant negative relationship between HIV knowledge scores and avoidant AIDS attitude scores (r=-0.2, p<0.01). The linear regression demonstrated for every one unit increase of AAS avoidant scores, HIV knowledge scores decreased 0.7 units (p<0.01); suggesting that students who scored higher in negative attitudes, achieved lower scores on HIV knowledge levels.
Conclusion: The study findings demonstrate the call to address this knowledge gap among a known population vulnerable to risky sexual behavior. Future research is needed such that HIV/AIDS awareness campaigns can be specifically tailored to the student population within the Ethiopian context.
Keywords: HIV/AIDS; Africa; Students; Gender; Knowledge; Attitudes; International Public Health; International Public Health